The effect of accelerated artificial aging on color change of three different types of composite (in vitro study) (Mustansiria Dental Journal, 2018)
The greater demand for esthetic in the modern life with the simplified bonding steps for composite filling increase its universal use but their gradual change in color over time make their replacement very important, the aim of this study is the comparison among different type of composite to see which type is the best color stability in the clinical work . Material and method :30 samples of three different materials have been made ,the first group is 10 samples fabricated from Filtek z250 ,the second group is 10 samples fabricated from Filtek z250xt and the third group is 10 samples fabricated from z350xt .All the samples color parameters were measured before placing in accelerated weathering tester (time 0)then all the samples were placed in the accelerated weathering tester for 150 h and 300h then the color parameters were measured from which the change in color had been measured. Statistical analysis was performed by using ANOVA repeated measure test to see if there were any significant difference among the ΔE of experimental groupsResults : the results show that the z250 have the highest color stability as compared with other types of composite used in this study while the z350xt results show the lowest color stability  also the result show that there's high significant difference among all groups among different time interval used in the studyConclusion: the change in color above the clinically acceptable threshold (3.3) was seen in all types of composite used in this study and that the z 250xt shows the least change in color.